2003
DOI: 10.1289/ehp.6341
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral performance and work experience in Florida farmworkers.

Abstract: Farmworkers experience many work-related hazards, including exposure to neurotoxicants. We compared neurobehavioral performance of 288 farmworkers in central Florida who had done farm work for at least 1 month with 51 controls who had not. Most of the farmworkers had worked in one or more of three types of agriculture: ornamental ferns, nurseries, or citrus fruit. We collected information on farm work history in a structured interview and evaluated neurobehavioral performance using a battery of eight tests. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 35 publications
5
73
2
1
Order By: Relevance
“…Neurobehavioral function was assessed in our study by using the WHO recommended neurobehavioral core test battery (NCTB) (World Health Organization, 1986;Anger, 2003). The NCTB is a widely used assessment established by WHO for early detection of neurotoxicity effects of compounds in the workplace.…”
Section: 3test Of Neurobehavioral Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurobehavioral function was assessed in our study by using the WHO recommended neurobehavioral core test battery (NCTB) (World Health Organization, 1986;Anger, 2003). The NCTB is a widely used assessment established by WHO for early detection of neurotoxicity effects of compounds in the workplace.…”
Section: 3test Of Neurobehavioral Functionmentioning
confidence: 99%
“…The NCTB is a widely used assessment established by WHO for early detection of neurotoxicity effects of compounds in the workplace. The NCTB provides a set of rapid, stable, and sensitive behavioral tests and is extensively used in neurotoxicology to assess changes of behavior in the presence of neurotoxic chemicals (World Health Organization, 1986;Anger, 2003 …”
Section: 3test Of Neurobehavioral Functionmentioning
confidence: 99%
“…90,91,[127][128][129] Even though intoxication with antiChEs may induce long-term mild changes in neurologic functions, the potential for low-level exposures that lead to chronic neurological changes is even less uncertain and a matter of diverse opinion. At this point, the question arises as to whether or not these effects are caused in doses below those causing acute toxicity or AChE inhibition.…”
Section: Long Term Cns Neurotoxicitymentioning
confidence: 99%
“…Studies in humans showed neurological, cognitive and psychomotor impairments following cumulative exposure to OPs and organochlorines in people from agricultural communities, without history of acute poisoning (Kamel & Hoppin 2004;Kamel et al, 2007). Neurobehavioural changes following low-dose OP exposure have been reported in sheep farmers (Stephens et al, 1995), greenhouse workers (Bazylewicz-Walczak et al 1999), tree-fruit workers (Fiedler et al, 1997), and farm workers (Kamel et al, 2003). These studies have found deficits in measures of sustained attention, information processing, motor speed and coordination.…”
Section: Introductionmentioning
confidence: 97%